(untitled) (Sains Humanika, 2019)
Conceptual knowledge is one of the mathematical knowledge areas which should be mastered by mathematics teachers besides factual, procedural, and metacognitive knowledge. Teachers are prone to cast conceptual knowledge aside and prioritise procedural knowledge without understanding the concepts which influence the options of mathematical strategies and models in the context of problem solving. A literature review was conducted to discuss past research findings in identifying secondary school teachers’ conceptual knowledge in the algebra topic. 68 past research articles were referred to and chosen based on the research purpose which was to investigate mathematics teachers’ conceptual knowledge level and its implementation in several mathematical topics quantitatively and qualitatively in local and international contexts.Â There have been a lot of researches conducted on teachers’ conceptual knowledge in several mathematical topics, however there is still a lack of research in investigating teachers’ conceptual knowledge on the algebra topic. Most of the past research findings showed that the teachers’ conceptual knowledge level was at a low level in several mathematicalÂ topics therefore a similar research is also needed in the algebra topic. This study can be extended to a more improved research in spite of the research sample, design or research methodology, instruments, and other factors. Â